Prospective study of robotic partial nephrectomy for renal cancer in Japan: Comparison with a historical control undergoing laparoscopic partial nephrectomy. (19th April 2018) - Tanaka, Kazushi; Teishima, Jun; Takenaka, Atsushi; Shiroki, Ryoichi; Kobayashi, Yasuyuki; Hattori, Kazunori; Kanayama, Hiro‐omi; Horie, Shigeo; Yoshino, Yasushi; Fujisawa, Masato
Abstract : Objectives: To evaluate the outcomes of robotic partial nephrectomy compared with those of laparoscopic partial nephrectomy for T1 renal tumors in Japanese centers. Methods: Patients with a T1 renal tumor who underwent robotic partial nephrectomy were eligible for inclusion in the present study. The primary end‐point consisted of three components: a negative surgical margin, no conversion to open or laparoscopic surgery and a warm ischemia time ≤25 min. We compared data from these patients with the data from a retrospective study of laparoscopic partial nephrectomy carried out in Japan. Results: A total of 108 patients were registered in the present study; 105 underwent robotic partial nephrectomy. The proportion of patients who met the primary end‐point was 91.3% (95% confidence interval 84.1–95.9%), which was significantly higher than 23.3% in the historical data. Major complications were seen in 19 patients (18.1%). The mean change in the estimated glomerular filtration rate in the operated kidney, 180 days postoperatively, was −10.8 mL/min/1.73 m 2 (95% confidence interval −12.3–9.4%). Conclusions: Robotic partial nephrectomy for patients with a T1 renal tumor is a safe, feasible and more effective operative method compared with laparoscopic partial nephrectomy. It can be anticipated that robotic partial nephrectomy will become more widely used in Japan in the future.